Beauvericin potentiates the activity of pesticides by neutralizing the ATP-binding cassette transporters in arthropods - Charbel Al Khoury (Nature Portfolio, 2021)
Abstract Multi-drug resistance is posing major challenges in suppressing the population of pests. Many herbivores develop resistance, causing a prolonged survival after exposure to a previously effective pesticide. Consequently, resistant pests reduce the yield of agricultural production, causing significant economic losses and reducing food security. Therefore, overpowering resistance acquisition of crop pests is a must. The ATP binding cassette transporters (ABC transporters) are considered as the main participants to the pesticide efflux and their neutralization will greatly contribute to potentiate failed treatments. Real-Time PCR analysis of 19 ABC transporter genes belonging to the ABCB, ABCC, ABCG, and ABCH revealed that a broad range of efflux pumps is activated in response to the exposure to pesticides. In this study, we used beauvericin (BEA), a known ABC transporters modulator, to resensitize different strains of Tetranychus urticae after artificial selection for resistance to cyflumetofen, bifenazate, and abamectin. Our results showed that the combinatorial treatment of pesticide (manufacturer’s recommended doses) + BEA (sublethal doses: 0.15 mg/L) significantly suppressed the resistant populations of T. urticae when compared to single-drug treatments. Moreover, after selective pressure for 40 generations, the LC50 values were significantly reduced from 36.5, 44.7, and 94.5 (pesticide) to 8.3, 12.5, and 23.4 (pesticide + BEA) for cyflumetofen, bifenazate, and abamectin, respectively. While the downstream targets for BEA are still elusive, we demonstrated hereby that it synergizes with sub-lethal doses of different pesticides and increases their effect by inhibiting ABC transporters. This is the first report to document such combinatorial activity of BEA against higher invertebrates paving the way for its usage in treating refractory cases of resistance to pesticides. Moreover, we demonstrated, for the first time, using in silico techniques, the higher affinity of BEA to ABC transformers subfamilies when compared to xenobiotics; thus, elucidating the pathway of the mycotoxin.